Analysis of human chromosome images: Application towards an automated chromosome classification. Issue 4 (30th April 2018) - Madian, Nirmala; Jayanthi, K. B.; Suresh, S.
Abstract: Karyotyping is the process of arranging the chromosomes to examine the chromosomal abnormalities, a solution for birth defects. Karyotype is achieved from analyzing the metaspread chromosome images. Metaspread chromosome images generally have problem related with overlapping and touching of chromosomes with each other. Segmentation and separation of overlapping and touching chromosomes are still an open issue. The paper proposes an automated algorithm to separate the touching chromosomes and overlapping chromosomes from G‐Band metaspread images. Segmentation is performed by obtaining the interesting (concave and convex) points on the image contour. A proper hypothesis is performed for separating overlapped and touching chromosome images. The isolation of overlapping and touching metaspread chromosome image helps in accurate automated chromosome classification to obtain a karyotype. The overall accuracy of the proposed method works well for separation of touching chromosome with 97.09% and overlapped chromosome with 95%.